Conformational space of 4,4′-methoxypropylstilbene molecule - Abulyaissova, L. K.; Kenzhetaeva, S. O.; Kasymova, M. S. (Pleiades Publishing, 2017)
Quantum-chemical simulation of the ground state [the density function B3LYP/6-31G, B3LYP/6-31G(d), and B3LYP/6-31+G(d,p) and the perturbation theory MP2/6-31G(d) methods] and the transition states [the B3LYP/6-31G(d) method] of 4,4′-methoxypropylstilbene molecule has been performed. Using the Ellinger MM2 force field method, the potentials of internal rotation have been obtained for each rotational degree of freedom of the molecule. The B3LYP simulation has revealed the planarity of the conjugated system and the orthogonal position of the alkyl substituent, whereas the benzene rings have deviated by about 20° with respect to the double bond plane according to the MP2 data. Three transition states of the molecule corresponding to the saddle points of the first and the second orders have been revealed. The stationary points have been identified by means of vibrational analysis.
Keywords: stilbene; conformational analysis; molecular mechanics; density functional theory